Metastatic bone tumors: Analysis of factors affecting prognosis and efficacy of CT and (18)F-FDG PET-CT in identifying primary lesions - SHIMADA, HIROFUMI (D.A. Spandidos, 2014)
We analyzed the prognostic factors in patients with metastatic bone tumors and evaluated the efficacy of different modalities in identifying the primary lesions. A total of 145 patients with bone metastases who attended the orthopaedic outpatient clinic were included in this study. The most frequent site of bone metastases was the spine. The primary tumor type was differently distributed between patients with a known primary tumor at the first visit and those with an unknown primary lesion. The number of breast cancer cases was statistically significantly lower in the primary-unknown group. However, the number of myeloma cases was significantly higher in the primary-unknown group. Survival was significantly lower in the skeletal-related events (SREs) compared to that in the non-SREs group. Furthermore, survival was significantly worse in patients with a performance status (PS) of ≥2 compared to those with a PS of ≤1 and neurological complications occurred statistically more often in the group with worse PS (≥2). Survival rates were significantly lower in the non-spinal compared to those in the spinal metastatic group. Since the majority of breast cancer patients presented with metastasis in the spine, a breast cancer origin was a positive prognostic factor in patients with spinal metastases. Although there were no significant differences between computed tomography (CT) and (18)F-fluoro-2-deoxyglucose ((18)F-FDG) positron emission tomography (PET)-CT in detecting primary lesions, CT may be the first choice due to its feasibility. In conclusion, lung cancer, SREs and worse PS were adverse prognostic factors for patients with bone metastasis. In addition, CT scans may be more useful for determining the primary lesion of a bone metastasis compared to (18)F-FDG PET-CT in a timelier manner.